Emotional experiencies and conditioning factors in elderly without couple relationship - Sandra Caridad Laurencio Vallina; Elena Jiménez Betancourt; Yailen Sánchez Masó (Centro Provincial de Información de Ciencias Médicas, 2017)
The emotional experiencies and conditioning factors of 2 elderly without couple relationship, belonging to "José Martí Pérez" Teaching Polyclinic in Santiago de Cuba are described. Both manifested negative emotional experiencies, given mainly by depression, loneliness, frustration and unhappiness, associated to their personal characteristics and worsened by belonging to a dysfunctional family. To such effects, an intervention strategy with individual, family and community approach was suggested, in order to contribute to the emotional well-being of this population group.